Examining Money Laundering in the Insurance Industry Through Fraud Heptagon Theory Perspective - Fadilah Fajar Bagaskara; Harti Budi Yanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Based on the principle of insurable interest, individuals and organizations enter into insurance agreements with the primary objective of securing protection against potential financial losses caused by unforeseen risks. However, according to various literature, insurance can also be utilized as a financial instrument for money laundering activities. This study aims to uncover potential indicators that may serve as opportunities for money laundering, analyzed through the lens of the Fraud Heptagon Theory, which includes the aspects of pressure, opportunity, rationalization, competence, arrogance, culture, and religion. This research employs a qualitative methodology with an interview approach, targeting individuals working within the insurance industry, such as insurance companies (internal auditors, insurance agents, underwriters), insurance brokers, and reinsurance companies to gain insights into the complex trade schemes. The implementation of Anti-Money Laundering (AML) measures is crucial to minimize the potential for money laundering and to ensure compliance with existing regulations.